2019
DOI: 10.32737/2221-8688-2019-1-58-65
|View full text |Cite
|
Sign up to set email alerts
|

PHASE DIAGRAMS OF THE FeGa2S4- FeIn2S4 AND FeS- FeGaInS4 SYSTEMS

Abstract: The phase equilibriums in the FeGa 2 S 4 -FeIn 2 S 4 and FeS-FeIn 2 S 4 systems were experimentally investigated by means of differential thermal and X-ray diffraction analyses. It found that they are quasi-binary and characterized by limited mutual solubility of starting compounds. The phase with composition FeGaInS 4 crystallizes in the FeGa 2 S 4 -type structure, melts at 1375 K without decomposition, and can be characterized as a congruently melting compound by its beh avior in the phase diagram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…The development and creation of new methods for directed synthesis of complex phases and materials require the study of phase equilibria in the corresponding systems [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The development and creation of new methods for directed synthesis of complex phases and materials require the study of phase equilibria in the corresponding systems [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The FeIn 2 S 4 ternary compound melts congruently at 1398 [25] or 1415 K [26], respectively, and crystallizes in the spinel structure (Sp.gr. Fd-3m) with the lattice parameters a = 1.0598 [27] or a = 1.053 nm [25].…”
Section: Introductionmentioning
confidence: 99%
“…The FeGaInS 4 compound also melts congruently (1375 K) and has a trigonal structure of the ZnAl 2 S 4 type (Sp.gr. P-3m1) with parameters: a = 0.37765, c = 1.22257 nm [26,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies of the phase equilibria in systems MX-Ga 2 X 3 -In 2 X 3 (M -Mn, Fe; X -S, Se, Te) were undertaken by us in order to search and develop the physicochemical basis for obtaining new magnetic semiconductors. The preliminary results obtained [21,22] showed the formation of wide regions of solid solutions along the MGa 2 X 4 -MIn 2 X 4 sections of these systems. However, an analysis of the literature data showed that the phase diagrams of some of the boundary quasi-binary components of these quasi-ternary systems require clarification.…”
Section: Introductionmentioning
confidence: 99%